Update on the management of severe hypertriglyceridemia – focus on free fatty acid forms of omega-3 - Pirillo A; Catapano AL (Dove Medical Press, 2015)
Angela Pirillo,1,2 Alberico Luigi Catapano2,3 1Center for the Study of Atherosclerosis, Bassini Hospital, Cinisello Balsamo, Italy; 2IRCCS Multimedica, Milan, Italy; 3Department of Pharmacological and Biomolecular Sciences, Università degli Studi di Milano, Milan, Italy Abstract: High levels of plasma triglycerides (TG) are a risk factor for cardiovascular diseases, often associated with anomalies in other lipids or lipoproteins. Hypertriglyceridemia (HTG), particularly at very high levels, significantly increases also the risk of acute pancreatitis. Thus, interventions to lower TG levels are required to reduce the risk of pancreatitis and cardiovascular disease. Several strategies may be adopted for TG reduction, including lifestyle changes and pharmacological interventions. Among the available drugs, the most commonly used for HTG are fibrates, nicotinic acid, and omega-3 polyunsaturated fatty acids (usually a mixture of eicosapentaenoic acid, or EPA, and docosahexaenoic acid, or DHA). These last are available under different concentrated formulations containing high amounts of omega-3 fatty acids, including a mixture of EPA and DHA or pure EPA. The most recent formulation contains a free fatty acid (FFA) form of EPA and DHA, and exhibits a significantly higher bioavailability compared with the ethyl ester forms contained in the other formulations. This is due to the fact that the ethyl ester forms, to be absorbed, need to be hydrolyzed by the pancreatic enzymes that are secreted in response to fat intake, while the FFA do not. This higher bioavailability translates into a higher TG-lowering efficacy compared with the ethyl ester forms at equivalent doses. Omega-3 FFA are effective in reducing TG levels and other lipids in hypertriglyceridemic patients as well as in high cardiovascular risk patients treated with statins and residual HTG. Currently, omega-3 FFA formulation is under evaluation to establish whether, in high cardiovascular risk subjects, the addition of omega-3 to statin therapy may prevent or reduce major cardiovascular events. Keywords: omega-3 fatty acids, eicosapentaenoic acid, docosahexaenoic acid, hypertriglyceridemia